Simulations in virtual reality: assessment of firefighters' decision-making competence - Reis, Vitor (2020)
This study focuses on the use of virtual reality simulations for the training of portuguese firefighters in emergency operations management and the assessment of decision-making competence. The research was carried out through the action-research method. In the first cycle a pilot training course was carried out in a group of eight trainers from the Portuguese National Fire Service School, in which data were collected on the performance of trainees and in the evaluation of training. In the last step, corrections and improvements to the training course were identified. In the second cycle of action-research the steps were repeated with the formal implementation of the training course for eight fire officers of several fire brigades in the country. Every trainee played the role of incident commander in two different training scenarios and their performance was assessed at both times using a common evaluation tool. The evaluation of the impact of the changes introduced in the second cycle was carried out through a comparative analysis of the learning assessments, the evaluations of the trainees of the two groups and the evaluation of the team of trainers. The results of the trainees' performance and the training evaluation allow to conclude that the training course promoted the development of decision-making competence in the management of emergency operations using virtual reality simulations.